2017
DOI: 10.1002/hpm.2475
|View full text |Cite
|
Sign up to set email alerts
|

Understanding ED performance after the implementation of activity‐based funding

Abstract: Substantial variation exists across Queensland EDs when resourcing service delivery in an activity-based funding environment. Historical inequity persists in the staffing profiles for regional and outer metropolitan departments. The lack of association between resourcing and performance metrics provides opportunity for further investigation of efficient models of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
1
1
Order By: Relevance
“…To a certain extent, ED staffing seems to positively correlate with workloads (Tables and ). This is similar to findings from a study in Queensland (Australia) with ED nursing staff (nursing per 1000 weighted activity units) correlated with total ED presentations . Exceptional status of university hospitals in our study was observed with fewer ED visits than the rest but a higher number of EPs, EM residents, and RNs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To a certain extent, ED staffing seems to positively correlate with workloads (Tables and ). This is similar to findings from a study in Queensland (Australia) with ED nursing staff (nursing per 1000 weighted activity units) correlated with total ED presentations . Exceptional status of university hospitals in our study was observed with fewer ED visits than the rest but a higher number of EPs, EM residents, and RNs.…”
Section: Discussionsupporting
confidence: 90%
“…This is similar to findings from a study in Queensland (Australia) with ED nursing staff (nursing per 1000 weighted activity units) correlated with total ED presentations. 12 Exceptional status of university hospitals in our study was observed with fewer ED visits than the rest but a higher number of EPs, EM residents, and RNs. This may suggest the influence of teaching status of university hospitals on the allocation of the human resource.…”
Section: Workforce Status Vis-à-vis the Workloadcontrasting
confidence: 46%
“…8 Furthermore, a recent analysis of ED 4-h performance failed to demonstrate a correlation with staffing levels or cubicle numbers, once again emphasising the importance of efficient ED workflows and the contribution of whole-of-hospital factors. 9 A variety of models of care (MOC) have been described in the literature that aim to address the effect of increasing demand on ED services. These models are often implemented in order to address a particular aspect of flow (i.e.…”
Section: Introductionmentioning
confidence: 99%